Multiple criteria hierarchy approach for analyzing competitiveness of States in Mexico - Alvarez, Pavel; Muñoz-Palma, Manuel; Miranda-Espinoza, Luz Eva; Lopez-Parra, Pavel; León-Castro, Ernesto (Unidad Editorial UPTC, 2020)
Competitiveness is related to welfare, economic progress and prosperity and has been an important topic for countries, enterprises, investors and citizens alike. This paper presents a new Multiple Criteria Hierarchy Process (MCHP) for rank the competitiveness of States in Mexico through the analysis of multiple criteria such as legality, economic, social, politic, governmental and environmental, precursors and international relations aspects. An important aspect of the new MCHP proposed is that considers the interaction between criteria and measure the performance of a large number of criteria. The study presents a competitiveness analysis of Mexican regions, regarding the interaction in different level of criteria hierarchy and evaluating the performance of 100 criteria to establish the competitiveness level of States in Mexico. Keywords: Multicriteria, hierarchy approach, competitiveness JEL Codes: C69, C81, D81 Received: 10/07/2020. Accepted: 05/11/2020.  Published: 01/12/2020